Seismic Expression of Shelf Breaks: Examples from Borneo/Kalimantan Basins - Herman Darman (Ikatan Ahli Geologi Indonesia, 2003)
Shelf break is a physiographic province in a basin defined by a change in dip from the shelf (dipping less than 1:1000 landward of the shelf edge) to the slope (dipping more than 1:40 seaward of the shelf edge). Vanney and Stanley (1983) described it is a point of the first major change in gradient at the outermost edge of the shelf, and its depth, distance from shore and configuration are highly variable. The shelf break is a distinct, critical interface of continental margins, which delineates the major physiographic boundary between two major submarine provinces, shelf and slope.Clinoform features and accordingly shelf breaks are expressed well in some seismic sections in the Tertiary basins surrounding Borneo or Kalimantan Island. Some seismic examples are taken from offshore Kutai, Tarakan, Sandakan, and NW Borneo basins. The depositional environments of the clastic systems of these basins range from fluvial to deepwater environment.